Mapping cyclo-dynamic dataflow into pipelined datapath - Molchanov, O. А.; Sergiyenko, A. M.; Vinokurov, A. I. (Problems of Informatization and Management, 2025)
The paper discusses the relevance of high-level synthesis (HLS) systems in designing pipelined datapaths. The goal of the research is to explore methods for mapping algorithms into a pipelined datapath that implements cyclic data flow graphs with dynamic schedules. The proposed method involves creating and optimizing cyclo-dynamic data flow graphs (CDDFG) and describing them in VHDL. A set of rules for arranging the correct CDDFG and respective finite state machine is proposed. The derived CDDFG is mapped into the pipelined datapath, as well as the synchronous dataflow. The method demonstrates its effectiveness through examples of run-length encoding decompression and LZW file decompression devices, which are implemented in field programmable gate arrays. The proposed method can be used manually or be implemented in HLS tools.